Cervical Spinal Cord Injury Associated With Neck Flexion in Posterior Cervical Decompression. Issue 5 (June 2019) - Sumiya, Satoshi; Kawabata, Shigenori; Ushio, Shuta; Tomizawa, Shoji; Sakaki, Kyohei; Hirai, Takashi; Yuasa, Masato; Inose, Hiroyuki; Yoshii, Toshitaka; Okawa, Atsushi
Abstract : Study Design: A retrospective analysis of prospectively collected data of 179 consecutive patients who underwent intraoperative neurophysiological monitoring during posterior cervical spine surgery for compression myelopathy. Objective: To evaluate preoperative factors in patients with deteriorating spinal cord function due to flexion of the neck during posterior cervical spine surgery by observing changes in waveforms on intraoperative monitoring. Summary of Background Data: We encountered several cases of intraoperative monitoring warning alerts because of neck flexion during posterior cervical spine surgery. We investigated the incidence rate and intraoperative predictors of deteriorating spinal cord function caused by neck flexion based on waveform changes. Materials and Methods: Subjects were 179 patients who underwent posterior cervical decompression for spinal cord compression. When warning alarms were set off by amplitude changes in the period between skin incision and exposure of the lamina, the neck position was changed from flexion to neutral, and patients whose electrical potentials recovered following cervical repositioning were placed in the flexion-induced potential reduction group. We then analyzed and extracted risk factors for flexion-induced reduction in electrical potentials. Results: In total, 156 patients were analyzed in this study. Monitoring alarms went off intraoperatively for 7 patients (4.5%) at the time of posterior cervical spine exposure. With regard to the most compressed level, the occupancy ratio of the anterior compression component, the kyphotic angle in flexion, and range of motion in the neutral position to flexion were significantly associated with flexion-induced reduction in electrical potentials. Furthermore, logistic regression analysis extracted the occupancy ratio of the anterior compression component at the most compressed level and the kyphotic angle of the most compressed level in flexion. Conclusions: Our findings suggest that a large anterior compression component and large kyphotic angle in neck flexion at the most compressed level are risk factors for intraoperative spinal cord injury during posterior cervical spine surgery.